G368(P) An audit of unplanned extubations in a paediatric intensive care unit. (May 2019) - Rennie, C; Keightley, J; Davidson, M; Hills, J; Worrall, M; Henderson, E; ,
Abstract : Background: The PICANET national average rate of unplanned extubation (UE) is 0.4 per 100 ventilator days. However, our Paediatric Intensive Care Unit is an outlier with a rate of 0.7 per 100 ventilator days in 2017. The accepted benchmark in the literature is a target of <1/100 ventilator days. Over recent years we have continued to see a rise in the total number of ventilator days. UE is an intensive care morbidity associated with risks such as prolonged admission and length of mechanical ventilation. A Quality Improvement group was therefore established. A new re-taping standard operating procedure was introduced in May 2017. Aim: Our aim was to identify any preventable causes of UE and define ways of reducing their incidence. Method: Retrospective collection of data was undertaken. Patient details for all UE from 2014 to 2017 were entered into an Excel spreadsheet. A total of 114 patients were included. Results: UE occurred most frequently in children aged <1 year within the first 5 days of admission. Oral extubations accounted for 63% of UE. Only 39% were receiving oral sedation. There was a lack of significant difference in the time of day when UE occurred. Only 15% of patients were highlighted to medical staff as having loose tapes and only 12% of cases had an incident form completed. Only 44% of UE required reintubation. Conclusions: We aim to reduce UE with interventions such as COMFORT scoring, training more staff in standard re-taping practices and nurse-led extubations. Early use of enteral sedation is being considered. Nasally intubating more patients could lower our UE, but this procedure is not without risk. With only 44% of UE requiring reintubation, efforts should be made to better identify readiness for extubation. We aim to continue to assess the impact of the new re-taping standard procedure by repeating this audit cycle.